Supporting investment decisions using data mining methods - Sysiak, Witold; Trajer, Jędrzej; Janaszek, Monika (Studia Informatica. System and information technology, 2009)
This paper presents an application of k-means clustering in preliminary data analysis which preceded the choice of input variables for the system supporting the decision about stock purchase or sale on capital markets. The model forecasting share prices issued by companies in the food-processing sector quoted at the Warsaw Stock Exchange was created in STATISTICA 7.1. It was based on neural modeling and allowed for the assessment of changes direction in securities values (increase, decrease) and generates the quantitative forecast of their future price.